Bioactivity Analysis of Lemongrass (Cymbopogan Citratus) Essential Oil - Mirghani, Mohamed Elwathig Saeed; Yahya, Liyana; Jamal, Parveen (2011)
Diseases such as diabetes mellitus and gout are among the chronic diseases affecting worldwide population. Investigation is required to find the alternative approaches to treat these chronic diseases, such as plant based medicine. In this study, lemongrass (Cymbopogan citratus) was chosen and examined on the basis of their usage in traditional medicines throughout Southeast Asia. GCMS analysis revealed the major constituents of the lemongrass essential oil which compromise 67.769% and 67.328% of the total oil respectively. Total phenolic content of the essential oil was analyzed by Folin Ciocalteau method and the results indicated that highest amount of phenolic content was obtained from essential oil extracted from lemongrasses stalk, with phenolic concentration of 2100.769 mg/l GAE. Anti oxidant activity was examined by DPPH scavenging test and the highest inhibition was obtained by essential oil extracted from lemongrass stalk (89.5%). β-glucosidase inhibition assay was carried out using an in-vitro model for anti diabetic test and lemongrass stalk essential oil showed highest degree of inhibitory activity (89.63%). Anti gout test was examined by xanthine oxidase inhibition (XOI) assay with the maximum percentage of xanthine oxidase inhibition of 81.34% obtained from lemongrass stalk essential oil. Thus this project aimed to find the potentiality of lemongrass essential oil which could be the alternative approach due to adverse effects with the use of synthetic drugs for the treatment of many forms of diseases.